(untitled) (Research, Society and Development, 2021)
Autistic Spectrum Disorder (ASD) defines a group of neurodevelopmental disorders, usually diagnosed in early childhood. During the last two decades an increasing increase in the prevalence of ASD has been detected. Hundreds of studies have been carried out, however, it remains unclear why the incidence of autism increased rapidly during the 1990s and continues to increase in the 2000s. A bibliographic survey was carried out in the following databases: PUBMED, LILACS and SCIELO between 2015 and 2020. The following descriptors were used: “Folic Acid” and “Autism Spectrum Disorder”. Initially, 46 articles were found. Of these, only 34 met the inclusion criteria and addressed aspects related to folic acid supplementation during the periconceptional period and its influence on the development of ASD. With regard to TEA and the administration of high doses of folic acid during the periconceptional period, it is concluded that further research is needed with appropriately standardized study designs and with adequate methodology before any definitive conclusions can be drawn. The results of recent clinical studies, although few and inconclusive, raise questions about adequate dosages or more targeted use of folic acid that need to be investigated.